PROMOTING THE BUCOVINA AREA ON CULTURAL AND RELIGIOUS TOURISM - Hincu, Liliana (Ecoforum Journal, 2017)
The Bucovina area is well-known nationally and internationally for the monasteries which are, most of them, included in the UNESCO heritage. It is an area full of history, well-known for local traditions and customs, such as: icons painted on glass, dying Easter eggs, carpet weaving or different braids, which reminds us of old traditions and customs that are still preserved from ancient times. Due to this inherited dowry, the tourist is delighted to visit these wonderful places, therefore the tourism agencies in the country and abroad set up different tourist programs, such as: circuits or pilgrimages, to enchant and attract tourists. The local agencies usually organize pilgrimages to the Monasteries in northern Bucovina, which are a special attraction for tourists. These monasteries are remarkable for their exterior and interior paintings, well preserved over the time and well-known for their vivid colours, suhc as: the Voronet Monastery is famous for the blue colour, also called the „Sistine Chapel”, and the cultural tourism is supported by knowing the traditions and customs available in the area.